KEPEMIMPINAN KEPALA SEKOLAH DALAM SUPERVISI KLINIS (Studi Situs SMP Negeri 1 Pedan Klaten) - Mujaedi , Mujaedi (2011)
This research general purpose is description of leadership wish to of headmaster in supervising clinic, while purpose of special description of leadership wish to of headmaster in planning of supervision clinic headmaster, leadership of headmaster in execution of supervision clinic headmaster, and leadership of headmaster in supervision feedback clinic headmaster. Approach this research is qualitative research, that is research about data collected and expressed in the form of words compiled in sentence. Research approach applies phenomenology. Research subject is headmaster and teacher. Data collecting method applies in-depth interview, observation, and documentation. Analysis data analytical technique interactive.. authenticity of data applies treeanggulation technique. Result of research that is : Planning of supervision clinic is part of implementation of leadership of headmaster to activity to influence people who is pointed to attainment of purpose of organization, one of them is execute enableness of teacher supervision in study, what expected can manage, observes and watch and assess teacher performance in study. Supervision clinic executed by headmaster with effective study activity, construction and tuition of planning activity, planning, execution, and its (the follow-up so that knowable teacher performance and follow u[, if there are still insufiency or weakness needs do construction and repair to reach minimum boundary of service learning, if have fulfilled minimum boundary, hence need to be improved. Feed beck of Supervision clinic is leadership characteristic of headmaster in executing supervision clinic in Junior High School State 1 Pedan Klaten by the way of tuition and construction democratically, charismatic, and familiarity, esteems teacher opinion, and co-ordinates to streamline supervision program pursuant to applied